IMPLEMENTATION OF POSITIVE MANAGERIAL CULTURE OF SCHOOL PRINCIPALS IN THE FORMATION OF 'DISCIPLINE AND ORDER' CHARACTER AT SMP NEGERI 1 ULUJAMI - Saguh Miliarto; Supandi; Harjito (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
Character education faces the challenge of degrading disciplinary values that demand a paradigm transformation of student management from a punitive to a restorative approach. This study aims to analyze the implementation of positive managerial culture of school principals in the formation of discipline and order character in SMP Negeri 1 Ulujami. The research uses a qualitative approach with a descriptive case study design. The subjects of the study include school principals, counseling guidance teachers, subject teachers, and students who  are determined purposively. The data collection technique integrates triangulation methods through structured in-depth interviews, participatory observations, and documentation studies. The data analysis adopts the interactive model of Miles, Huberman, and Saldana which includes data condensation, data presentation, and conclusion drawing by cross-verification between sources. The results of the study show that the implementation of a positive culture is carried out through planning that integrates values into the vision and mission, organization by placing the counseling guidance team as the lead mediator, implementation through daily habituation programs, and continuous supervision through exit interviews as well as analysis of violation data. This implementation has proven to be effective in changing student behavior from extrinsic compulsion to a sustainable intrinsic habit